Report on the Ornithological Expedition in Northwest Greenland 1965. - Joensen, Anders Holm; Preuss, Niels Otto (Meddelelser om Grønland, 1972)
The Ornithological Expedition to Northwest Greenland 1965 visited Sarqaqdalen in the northern part of Disko Bugt in early July and carried out a general faunistic survey of the bird life and an intensive census of the breeding passerine population in a 152 hectare plot. From medio July to the end of August the expedition surveyed Upernavik District with special emphasis on the distribution and size of seabird colonies. Most of these were visited, including the huge Uria lomvia colony at Kap Shackleton (Agparssuit) with abt. one million birds. The observations in 1965 are compared with the observations by SALOMONSEN in 1936.